#TITLE_ALTERNATIVE# - AJI (NIM: 24907006), BINTORO
In 2008, a CFD open source software had been released by EDF R&D of France called Code_Saturne under terms of GNU General Public License. Code_Saturne is a single phase CFD software that has been validated in about 30 cases. A study of Code_Saturne application for buoyancy driven natural convection in sub channel was performed in this thesis. The objective of the study was to validate and test the CFD open source software in solving the natural convection problem in a sub channel. The goal of the validation was application of the code to simulate the natural convection in a sub channel. The method employed was quantitative validation by numerical solution verification and comparison to experimental data. Verification was done to assess the numerical simulation uncertainty by the method of Grid Convergence Index (GCI). Validation was completed by comparing the simulation result to the experimental result of natural convection in square cavity performed before. The experiment used a water filled cube with the two facing sides were maintained in their respective constant temperatures in order to provide a natural convection flow. Several monitoring point were observed to obtain temperature and flow data. A model was built to simulate the same condition with Code_Saturne. The validation demonstrated that Code_Saturne was able to simulate natural convection in square cavity satisfactorily and most likely could be used for application of natural convection simulation in a sub channel. The objective of the application was to test that the validation result in a square cavity was applicable to simulate the natural convection in a sub channel.